Utilidad del modelo 5MPB-Toledo para predecir bacteriemia en el paciente anciano - Agustín Julián-Jiménez (Asociación Colombiana de Infectología, 2021)
Objective: To analyse a risk score to predict bacteremia (MPB5-Toledo) in the patients aged older 65 years seen in the emergency departments (ED) due to infections.Patients and Methods: Prospective and multicenter observational cohort study of the blood cultures (BC) ordered in 66 Spanish ED for patients aged older 65 years seen from December 1, 2019, to April 30, 2020. The predictive ability of the model was analyzed with the area under the Receiver Operating Characteristic curve (AUC-ROC). The prognostic performance for true bacteremia was calculated with the cut-off values chosen for getting the sensitivity, specificity, positive predictive value and negative predictive value.Results: A total of 2.401 blood samples wered cultured. True cases of bacteremia were confirmed in 579 (24.11%). The remaining 1.822 cultures (75.89%) wered negative. And, 138 (5.74%) were judged to be contaminated. Low risk for bacteremia was indicated by a score of 0 to 2 points, intermediate risk by 3 to 5 points, and high risk by 6 to 8 points. Bacteremia in these 3 risk groups was predicted for 1.2%, 18.1%, and 80.7%, respectively. The model ́s area under the receiver ope-rating characteristic curve was 0.908 (95% CI, 0.897-0.924). The prognostic performance with a model ́s cut-off value of ≥ 5 points achieved 94% (95% CI: 92-96) sensitivity, 77% (95% CI: 76-79) specificity, and negative predictive value of 97% (95% CI: 96-98).Conclusion: The 5MPB-Toledo score is useful for predicting bacteremia in the patients aged older 65 years seen in the emergency departments due to infections.